MPC-Based Prediction of Anti-Mutant Effectiveness of Antibiotic Combinations: In Vitro Model Study with Daptomycin and Gentamicin against Staphylococcus aureus - Maria V. Golikova; Elena N. Strukova; Yury A. Portnoy; Stephen H. Zinner; Alexander A. Firsov (Antibiotics, 2021)
To explore whether combined treatments with daptomycin and gentamicin can prevent the development of Staphylococcus aureus resistance, and whether the possible restriction is associated with changes in antibiotic mutant prevention concentrations (MPCs), the enrichment of daptomycin- and gentamicin-resistant mutants was studied by simulating 5-day single and combined treatments in an in vitro dynamic model. The MPCs of the antibiotics in the combination were determined at concentration ratios equal to the ratios of 24 h areas, under the concentration–time curve (AUCs) of the antibiotics, as simulated in pharmacodynamic experiments. The MPCs of both daptomycin and gentamicin decreased in the presence of each other; this led to an increase in the time when antibiotic concentrations were above the MPC (T>MPC). The increases in T>MPCs were concurrent with increases of the anti-mutant effects of the combined antibiotics. When anti-mutant effects of the antibiotics in single and combined treatments were plotted against the T>MPCs, significant sigmoid relationships were obtained. These findings suggest that (1) daptomycin–gentamicin combinations prevent the development of S. aureus resistance to each antibiotic; (2) the anti-mutant effects of antibiotic combinations can be predicted using MPCs determined at pharmacokinetic-based antibiotic concentration ratios; (3) T>MPC is a reliable predictor of the anti-mutant efficacy of antibiotic combinations.